Synthesis and evaluation of delayed anti-high temperature gel plugging agent - Bai, Yang; Wu, Lingfeng; Luo, Pingya; Li, Daoxiong (Frontiers in Energy Research, 2022)
The malignant leakage of complex formations seriously restricts the drilling time and has become a major drilling technical problem that needs to be solved urgently at this stage. In particular, the malignant leakage of large fractures and fractured formations is difficult to construct, and the success rate of plugging is low. In this paper, according to the above formation conditions, by analyzing the leakage mechanism of the malignant leakage formation, the method of plugging the large fractures and broken fractured formations is summarized. The adiabatic copolymerization co-hydrolysis method was used as the gel synthesis method, 2-methacrylic acid amide and acrylamide (AM) were used as the main raw materials, and the redox initiation system composed of sodium sulfate and sodium bisulfite was used as the initiator. Using its redox initiation characteristics, high-strength bonding between organic polymer covalent bonds was achieved by a self-made cross-linking agent; using the thermoplasticity of hot-melt adhesive, the initiator is wrapped in hot-melt adhesive particles to achieve high-temperature slow-release initiation, and finally, a gel plugging agent with good compatibility with drilling fluid, controllable gel formation time, stable gel formation, and good gel breaking performance was synthesized, which is suitable for severe lost circulation under high-temperature and high-pressure conditions. A compatibility study of gel and common drilling fluid systems, the effect of temperature on gel formation, gel rheological properties under high temperature and high pressure, gel start-up pressure, and gel breakability tests were evaluated under laboratory conditions. The experimental results show that the gel has good compatibility with common drilling fluid systems; with the increase of temperature, the gel time of the gel plugging agent gradually decreases, and the gel time can be adjusted from 1 to 3 h at a high temperature of 150°C; when the concentration of the gel in the experimental slurry exceeds 2%, its rheological properties change abruptly; under certain conditions, the starting pressure of the gel can reach up to 6.5 MPa; and under the condition of 150°C, the gel breaking rate was over 98% after 24 h. Various experiments show that the gel’s performance meets the requirements for plugging malignant leakage formations, and the effect is good. Compared with traditional gel materials, the gel plugging agent synthesized in this paper has the characteristics of a simple configuration process and superior performance with drilling fluid, which provides a new idea for malignant leakage plugging.